Tocilizumab Treatment for Nephrotic Syndrome Due to Amyloidosis in Behcet's Disease. (May 2013) - Redondo-Pachón, M.D.; Enríquez, R.; Sirvent, A.E.; Andrada, E.; Noguera-Pons, R.; Millán, I.; Amorós, F.
<x xml:space="preserve">Abstract</x> Renal involvement is an unusual but significant Behcet´s disease (BD) complication and AA amyloidosis appears to be the most common etiology. IL-6 is a pro-inflammatory cytokine with an important role in AA amyloidosis development. Tocilizumab (TCZ) is a humanized anti-IL-6 receptor antibody that has emerged as an effective and specific treatment in AA amyloidosis secondary to chronic inflammatory disorders. We report on a patient diagnosed with BD who developed nephrotic syndrome caused by renal AA amyloidosis with an excellent response to TCZ therapy.